using research evidence to improve gender based planning, budgeting and implementation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The CCAFS sponsored Policy Action for Climate Change Adaptation (PACCA) using the learning alliances at the various levels has worked with various policy makers and other stakeholders at the various levels to improve gender budgeting that has improved climate change actions for thousands of people.